(3CSeGA hUaGJ Gddgs - (3CHh HcQ CMeO Hf GdMSjf Hf Ydj GdNQGSGfj GdTGaYj, GdHjgbj,J (B458 (3g` s ((3CHh GdMSf Ydi Hf eMeO Hf Ydi Hf CHj HcQ GdLQLGfi s)
(3ChdgG (B:s
(3bGd GdGSJGP GdGeGe GHh HcQ CMeO Hf GdMSjf GdHjgbi QVi Gddg Yfg cJGH GSeGA Gdgd Ld KfGDg hUaGJg GdJi Od cJGH Gddg SHMGfg hJYGdi Ydi EKHGJgG GhOdJ Ydjg SfI QShd Gdgd Udi Gddg Ydjg hSde s
(3BNQgG (B:s
(3bGd SeYJ QShd Gddg Udi Gddg Ydjg hSde jbhd (B:" (3cGf bHdce YHO GJGg Gdgd eGdkG hhdOkG aPcQ GdMOjK hbGd Ke PQhfi ai jhe QjM YGUa dYdi GVd Gddg bGd aaYdhG bGd NTjJc Gi QH bGd GSeYc QGgHkG aJHJ Ydjg hGdMeO ddg QH GdYGdejf s
(3GdcJGH Je WHYgs
(3bQf GdfSN (B:s
(3GdbQf GdSGOSs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B1 - (3U (B116 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B1 - (3U (B206s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdMOjK h GdeUWdMs